Practice theory in consumption studies: a biblioshiny review (Gestão & Regionalidade, 2024)
The Practice Theory presents relevant contributions to the understanding of consumption phenomena. Analyzing practice elements (materials, competencies, and meanings), different human activities can be interpreted. However, it is still necessary attention to which themes can be developed within the management area. The present study sought to perform a bibliometric analysis of Practice Theory and Consumption themes within the management field. A bibliometric analysis was carried out based on Scopus and Web of Science databases. The Biblioshiny tool was used to perform descriptive, co-citation, and thematic clustering analysis. Four thematic groups were identified, encompassing sustainable consumption practices, collaborative consumption practices, purchasing practices, and food practices and green-marketing. Important themes for future studies are directed to purchasing practices and food consumption. New research directions can be used based on the analyzed data.
Keywords: Practice Theory; Consumption; Biblioshiny